THE DEBATE ON THE IMPLEMENTATION OF NE BIS IN IDEM PRINCIPLE IN HANDLING THE CORPORATE CRIME IN INDONESIA - Timbo Mangaranap Sirait (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractSince the issuance of Temporary People’s Consultative Assembly Decree - TAP MPRS No. XXIII/66 until the Reformation era, the participation of strategic multinational corporations is needed for the development. However, in doing their activities, there was a corporation who committed bribery whose criminal law jurisdiction is related to Anti-Bribery FCPA of America. Although the bribery beneficiaries were sentenced in Indonesia because of the locus and tempus delicti of the crime was in Indonesia, since such corporation was convicted first in the US, the corporation is no longer able to be prosecuted in Indonesia because of Ne Bis In Idem.IntisariSejak terbitnya TAP MPRS No. XXIII/66 hingga era Reformasi, partisipasi korporasi multinasional dalam pembangunan sangat strategis diperlukan. Akan tetapi dalam kegiatannya ada korporasi melakukan tindak penyuapan yang yurisdiksi hukum pidananya ada titik-taut dengan Anti-Bribery FCPA Amerika. Walaupun penerima suap sudah divonis di Indonesia karena locus dan tempus delicti adalah Indonesia, tetapi karena korporasi penyuap mendadak lebih dahulu diputus bersalah di Amerika, telah berimplikasi korporasi tersebut tidak dapat lagi diadili di Indonesia karena Ne Bis In Idem.